Great expectations: Banks as equity underwriters - Chaplinsky, Susan; Erwin, Gayle R. (Journal of Banking & Finance, 2009)
We examine the in-roads commercial banks have made into equity underwriting over 1990–2002. While banks end the period handling upwards of 25% of equity underwriting, this increase results almost exclusively from acquisitions of investment banks with an already established market share of equity underwriting. We find a significant decline in the market share of equity underwriting that banks acquired in the post-merger period, a decline that is larger than that experienced by independent investment banks of comparable reputation. Banks lose market share because they originate fewer IPOs and their IPOs have a lower incidence of follow-on SEOs compared to independent investment banks. Following the merger, banks experience a large fall off in their ability to retain follow-on SEOs and are less successful in winning SEO mandates when an issuer switches from its IPO underwriter. Overall, the findings suggest it has been difficult for banks to achieve scope economies in equity underwriting.